The Impact of Risk Factors in Food and Beverage Processing on the Incident of Stunting in Children - Maryam A Latona; Budiman (Journal of Health Literacy and Qualitative Research, 2021)
Stunting is an abnormal condition of the body caused by more than one factor (multifactorial). the combination of inadequate sanitation and unsafe drinking water quality and poor food sanitation hygiene behaviour is a risk factor for stunting. The purpose of this study was to determine the risk factors for drinking water treatment and food processing with the incidence of stunting in children under five in Kalora Village. This type of research is an analytical observational approach, case control research design. The sample size is 104 case and control respondents with total sampling technique. To assess the effect of the two variables, univariate analysis and bivariate analysis were used. The test used for bivariate analysis is the Odd Ratio (OR) test. The results of this study are drinking water treatment is a risk factor for stunting with an OR value of 5.296 (OR> 1), meaning that households that carry out drinking water treatment processes that are not good will have a 5.3 times higher risk of stunting compared to households that do not use drinking water properly. good drinking water treatment. Food processing is a risk factor for stunting with an OR value of 26.278 (OR> 1), meaning that households that process food processing that is not good will have a 26.3 times higher risk of stunting compared to households with good food processing. From the results of this study, it is hoped that the relevant Regional Apparatus Organizations will synergize and improve comprehensive promotive and preventive efforts in terms of stunting prevention in the Kinovaro Health Canter area.